Color temperature tunable white light based on monolithic color-tunable light emitting diodes - El-Ghoroury, Hussein S.; Nakajima, Yoshitake; Yeh, Milton; Liang, Evan; Chuang, Chih-Li; Chen, J. C. (Optics express, 2020)
A color-temperature tunable white light-emitting diode (LED) based on a newly developed monolithic color-tunable LED structure was demonstrated. The color-tunable LED structure consists of three different sets of quantum wells separated by intermediate carrier blocking layers that can independently emit visible lights from 460 to 650 nm under different injection currents. To generate white light, the color-tunable LED is operated under pulsed conditions with each pulse consisting of multiple steps of different current amplitudes and widths emitting different colors. The combined spectrum of different colors is aimed to mimic that of the blackbody radiation light source. The pulse rate is designed to be higher than the human eye response rate, so the human eye will not discern the emission of successive colors but a singular emission of white light. Results of a two-step pulse design show this method is able to generate white light from 2700 K – 6500 K. Moreover, their color coordinates fall within the 4-step MacAdam ellipses about the Planckian locus while achieving the Color Rendering Index (CRI) in the 80-90 range. Finally, simulations show improvement of CRI into the 90-100 range is possible with further optimization to the color-tunable LED spectral emission and use of three-step pulses.